Aprovechamiento de vertebrados terrestres por las poblaciones humanas que habitaron la costa del Golfo San Matías (Río Negro, Argentina) durante el Holoceno tardío - Marani, Hernán A. (Access archaeology., 2018)
This book presents the results and discussion of archaeofaunal studies which took place in the northern San Matías Gulf (Rio Negro Province) during the last six years, focussing on terrestrial mammals and birds.